RESPON MASYARAKAT TERHADAP PROGRAM DANA DESA DI DESA HUTA DAME KECAMATAN PANYABUNGAN UTARA KABUPATEN MANDILING NATAL - Wantina Wantina; Husni Thamrin (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2022)
Government Regulation No.60 of 2014 on Village Funds sourced from the State Budget of Revenue and Expenditure designated for Villages used to finance the implementation of governance, development implementation, community development, and empowerment Community.Village Fund programs are implemented throughout the province in Indonesia, one of them is in North Sumatra Province. The implementation of the Village Fund Program begins in 2015 of which approximately 74,093 villages participated in the program. One village that got the Village Fund program is Huta Dame Village, North Panyabungan District, Mandailing Natal Regency.The Village Fund program raises a community response, which can be seen from three aspects, namely perception, attitude and participation.Considering this, of course the community will give different responses to the Village Fund program in Huta Dame Village.The research method used descriptive research, which is to create a comprehensive picture of how the community response to the Village Fundprogram in Huta Dame Village. This research was conducted in Huta Dame Village, North Panyabungan District, Mandailing Natal Regency with 30 respondents. Data collection techniques through observation and questionnaires distributed to respondents. While the analytical method used is descriptive, check the questionnaire of the respondents then look for the frequency and percentage arranged in single table forms are described quantitatively and using scales Likert to measure the variables.Based on data that has been collected and analyzed it can be concluded that the average Village Fund program received a positive response from the people of Huta Dame Village with a value of 0.59.Consisting of perceptions of value 0.71, attitude with value 0,77 and participation with value 0,31.